Enabling Real World Scale Structural Superlubricity All-Atom Simulation on the Next-Generation Sunway Supercomputer - Duan, Xiaohui; Wang, Jin; Gao, Ping; Ma, Ming; Gan, Lin; Liu, Xin; Fu, Haohuan; Xue, Wei; Chen, Dexun; Yang, Guangwen; Liu, Weiguo (International Conference for High Performance Computing, Networking, Storage and Analysis (Online), 2023)
Molecular dynamics (MD) simulation can provide an affordable way for inspecting microscopic phenomena, which is a powerful complement to real-world experiments. But the spatial scale of MD simulations is usually magnitudes smaller than experiment systems. In this paper, we present our work, redesigning the widely used inter-layer potential in structural superlubricity. By carrying out a specialized neighbor list for inter-layer potential computation, the total memory access amount is reduced significantly. Besides, a simple but efficient vectorization strategy is implemented based on the new neighbor list. In the extreme case, our work can scale to 38 million cores to achieve a sustainable performance of 61 PFLOPS, enabling a simulation of a superlubricity system of 32\ μ m^{2} with 7.2 billion atoms at 4.75\ ns/day , which is 11,834 times of reported largest scale simulation in superlubricity systems in contact area and almost ten times faster in time-to-solution. Furthermore, we have done a simulation at 9\ μ m^{2} which results in consistency with real-world experiments and verified some theoretical predictions in the mesoscopic scale.